Commentary on the Portfolio of Compositions - CZERNIAK, ELIS (Trinity College Dublin. School of Creative Arts. Discipline of Music, 2018)
This thesis, comprised of a portfolio of compositions accompanied by media examples and commentary, traces the evolution of the author?s compositional approach in the search for a manner to present unstable sound that allows its natural acoustic phenomena and their interrelations to be experienced at the forefront. The controlling factors discussed are not just the physical properties of sound, but also how it is perceived. The written commentary presents, in detail, specific examples of how and why this has been achieved, with the main focal points being: limited unstable timbral palettes, different forms of listening and perception, collaboration and performative aspects, controlled improvisation and notation abandonment. With regard to these elements, a point must be made that, although there are developments within each, the musical goal remains the same, with the exploration of unstable sound and the complex timbres within, and its correlation with the unification of composer, performer and listener, being the main goal within the musical environment.
APPROVED
Keywords: Music Composition; Improvisation; Performance; Experimental Music